TINDAKAN SAFEGUARD DALAM PASAR BEBAS ASEAN SEBAGAI UPAYA PERLINDUNGAN INDUSTRI DALAM NEGERI - Theresia L Pesulima (SASI, 2017)
The provisions concerning the Safeguard action are mentioned in Article 3 (8 f) Trade In Goods Framework Agreement on Comprehensive Economic Cooperation Beyond the Association of South Asian Nations and the People's Republic of China as ratified by Presidential Decree number 48 of 2004 Concerning the Agreement on the Framework for Comprehensive Economic Cooperation Between the Member States of the Association of Southeast Asian Nations and the People's Republic of China, article 3 point 8 (f) which refers to the GATT principle. This safeguard is a form of protection against the domestic industry that suffers loss or threat of loss caused by increased imports by limiting imported goods whose imports are increasing. In safeguard implementation in Indonesia, security measures shall comply with the requirements set forth in Articles 3 to 8, as well as Article 11 ofÂ  Keppres number 84 of 2002 concerning the Safeguard Measures of Domestic Industries Due to the Increase in Import Imports. The Regulation governs the determination of serious harm and / or threat of serious harm to domestic industry due to the surge of imports of investigated goods shall be based on the analysis of all related factors objectively and measurably from the industry.